"I'm a fat bird and I just don't care": A corpus-based analysis of body descriptors in plus-size fashion blogs. (October 2019) - Limatius, Hanna
Abstract: Plus-size women have traditionally been, and continue to be, in a marginalized position in contemporary Western societies. This marginalization is especially visible in the field of fashion, since mainstream fashion media promotes thinness as the bodily ideal for women. However, the field of fashion is slowly but surely becoming more diverse in its representation of beauty. Fashion blogs, along with other social media platforms, are instrumental to these changes. Through blogging, plus-size women can actively participate in constructing new fashion discourses, as well as forming communities around their shared interest in fashion. One way of reconstructing the hegemonic discourses built around fashion and being plus-size is the reappropriation of words used to describe the plus-size body, such as "fat". In this article, I apply corpus-linguistic methodology to investigate the role of body descriptors in twenty UK-based, plus-size fashion blogs. The frequency and distribution of forty-five terms that are used to describe a plus-size woman's body in a self-compiled blog corpus are discussed alongside qualitative examples from blog texts. The results of the study reveal the variety within the genre of plus-size fashion blogs: fat acceptance activism influenced bloggers use certain body descriptors more than bloggers who focus on fashion trends and personal style. The study highlights the importance of combining qualitative and quantitative methods in research on online communities.